Body Mass Index and Tumor-Infiltrating Lymphocytes in Triple-Negative Breast Cancer. (6th July 2020) - Floris, Giuseppe; Richard, François; Hamy, Anne-Sophie; Jongen, Lynn; Wildiers, Hans; Ardui, Jan; Punie, Kevin; Smeets, Ann; Berteloot, Patrick; Vergote, Ignace; De Croze, Diane; Meseure, Didier; et al.
Abstract: Background: High levels of stromal tumor-infiltrating lymphocytes (sTIL) are associated with increased pathological complete response (pCR) rate and longer survival after neoadjuvant chemotherapy in triple-negative breast cancer (TNBC) patients. Here, we evaluated the value of sTIL in predicting pCR and explored prognosis in TNBC patients treated with neoadjuvant chemotherapy according to body mass index (BMI). Methods: sTIL were scored centrally on pretreatment biopsies from 2 retrospective series of nonunderweight TNBC patients (n = 445). sTIL and BMI were considered as binary (sTIL: <30.0% vs ≥30.0%; BMI: lean vs overweight and obese) and continuous variables. Associations with pCR (ypT0/isN0) were assessed using logistic regression, and associations with event-free survival and overall survival were assessed using Cox regressions. Results: 236 (53.0%) patients were lean and 209 (47.0%) overweight and obese. pCR was achieved in 181 of 445 (41.7%) patients. Median sTIL was 11.0%, and 99 of 445 (22.2%) tumors had high sTIL. A statistically significant interaction between sTIL and BMI, considered as categorical or continuous variables, for predicting pCR was observed in the multivariable analysis ( P interaction = .03 and .04, respectively). High sTIL were statistically significantly associated with pCR in lean (odds ratio [OR] = 4.24, 95% confidence interval [CI] = 2.10 to 8.56; P < .001) but not in heavier patients (OR = 1.48, 95% CI = 0.75 to 2.91; P = .26) in the multivariable analysis. High sTIL were further associated with increased event-free survival in lean (hazard ratio [HR] = 0.22, 95% CI = 0.08 to 0.62; P = .004) but not in heavier patients (HR = 0.53, 95% CI = 0.26 to 1.08; P = .08). Similar results were obtained for overall survival. Conclusion: BMI is modifying the effect of sTIL on pCR and prognosis in TNBC patients treated with neoadjuvant chemotherapy.